Effect of Current Ratio and Debt to Asset Ratio on Return On Asset Moderated by Firm Size - Anggraini Syahputri; Hendrick Sasimtan Putra; Julyanthry Julyanthry; Eka Purnama Sari; Debi Eka Putri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of Current Ratio (CR), Debt to Asset Ratio (DAR) on Return On Asset (ROA) moderated by Firm Size (SIZE) on Index IDX 30 Companies Listed on Indonesia Stok Exchange for 2017-2020 period. Data analysis in this study was carried out statistically and statistically inferential. Statistical analysis includes multiple linear regression analysis, classical assumption test, t-test, and hypothesis which Multiple Regression Analysis does. The hypothesis testing results are partially carried out, namely the t-test shows that CR has a positive and insignificant effect on ROA. DAR partially has a positive and significant effect on ROA. Thus the result from moderating analysis, SIZE can moderate the effect of CR on the ROA but SIZE can’t moderate the DAR on ROA of Index IDX 30 Companies for the 2017-2020 period.